The trustworthy of Halal Logo on imported food in Malaysia / Farah Hazween Amanah, Abdul Rauf Ridzuan and Nur Ain Atieqah Baharudin - Amanah, Farah Hazween; Ridzuan, Abdul Rauf; Baharudin, Nur Ain Atieqah (Faculty of Communication & Media Studies, 2019)
This research examined the study of the trustworthy of Halal Logo on imported food in Malaysia as the main option. Descriptive quantitative research study was conducted through survey using questionnaire form. The Independent Variable based on the main dimension which is the reliability imported food’s Halal Logo. There are four factors (1) Company Background (2) Food Labelling (3) Knowledge (4) Marketing while Dependent Variable is trustworthy on Halal Logo’s food to measure the trustworthy of Halal Logo on imported food among community in Malaysia. The study has involved with 200 respondents. The suitable research theory that implemented throughout the study is Social Cognitive Theory by Badura and Walters. This study towards perceptions behaviour, environmental factors and personal factors to measure the trustworthy of Halal Logo on imported food among community in Malaysia. The hypothesis testing gained by using two different methods which indicated different result which are Pearson Correlation and Multiple Linear Regression. Based on the research by using Pearson Correlation method the four listed null hypothesis is accepted based on the standardized significant values which is must be less than (p= 0.05). However, based on Multiple Linear Regression method, there are two different reading which formed different results. The first result is based on Beta value which shown the most significant relationship between independent towards dependent variables. Thus, the result indicated Marketing is (β =.507) the strongest relationship towards dependent variables. However, based on significant value in Coefficient Multiple Regression analysis, the null hypothesis of knowledge (p= .014) and marketing (p= .000) is being accepted with significant value below than (p= 0.05).